Finansowanie działalności samodzielnych publicznych zakładów opieki zdrowotnej lecznictwa stacjonarnego - Zaleska, Beata (Funding of the Independent Public Units of Stationary Medical Care, 2007)
National health insurance system, introduced on 1st January 1999, has brought about a change in the administrators of the finances at a central level. What is characteristic of the new system is the financing of the medical service by the insurance funds which collect money from the premiums, compulsory payments by employers and employees. The health insurance system makes the state act as a supervisor creating the frames of the system's functioning. The only way to obtain the entitlement to the service provided by the health funds is to sign an insurance contract and, in consequence, to pay the premiums. The introduction of the system has also influenced the way health care centres are financed, among which medical care units of stationary treatment or else hospitals play a vital role. The institutions in question absorb the majority of financial resources allocated for the health care system. The funding of the hospitals is based on a contract system. It is indispensable to set the rules and the ways of contracting so that the hospital could fully perform the functions it is made for, in other words to cater for everyone in need. The article presents the ways in which hospitals all over the world (Poland included), are financed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 476-487